Evaluation of dental emergency outcomes of the Oral Health Fitness Classification of the South African Military Health Service (SAMHS) in Gauteng - South Africa - Van Wyk, Philippus J. (University of Pretoria, 2013)
Dissertation (MChD)--University of Pretoria, 2012.